2021
DOI: 10.1016/j.cell.2021.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and functional interrogation of SARS-CoV-2 RNA-host protein interactions

Abstract: Highlights d ChIRP-MS of SARS-CoV-2 RNA identifies viral RNA-host protein interaction networks d Comparative analysis identifies SARS-specific and multiviral RNA-protein complexes d SARS-CoV-2 interactome-focused CRISPR screens reveal a broad antiviral response d Host mitochondria serve as a general organelle platform for anti-SARS-CoV-2 immunity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
206
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(221 citation statements)
references
References 78 publications
13
206
1
1
Order By: Relevance
“…RBPs are likely candidates for host factors involved in the response of human cells to SARS-CoV-2, as well as viral manipulation of host machinery. During preparation of this study, two experimental studies 85,86 reported hundreds of proteins that interact with SARS-CoV-2 RNA in human liver-derived cell lines. Encouragingly, they validated binding of several candidate proteins highlighted by our analysis (Table 2 and Supplementary Data 13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RBPs are likely candidates for host factors involved in the response of human cells to SARS-CoV-2, as well as viral manipulation of host machinery. During preparation of this study, two experimental studies 85,86 reported hundreds of proteins that interact with SARS-CoV-2 RNA in human liver-derived cell lines. Encouragingly, they validated binding of several candidate proteins highlighted by our analysis (Table 2 and Supplementary Data 13).…”
Section: Discussionmentioning
confidence: 99%
“…Selected human RBPs whose putative binding sites are enriched in regions of the SARS-CoV-2 genome, along with experimental information. Log2 fold change is reported only for differentially expressed genes (DEGs) with FDR-adjusted p-value < 0.05. scRNA indicates whether the RBP is co-expressed with ACE2 and TMPRSS2 in single-cell RNA-seq data from human lung cells55 ; PPI Map indicates reported interaction with a SARS-CoV-2 viral protein18 ; viral RNA binding indicates RBPs experimentally found to interact with SARS-CoV-2 RNA in a human liver cell line85,86 . UTR untranslated region.…”
mentioning
confidence: 99%
“…1C, Supplementary Table 1). Proteins recently identified in genome-wide interactome studies as direct RNA interaction partners for SARS-CoV-2 were selected for downstream functional characterization 3,[20][21][22] . Several of these have been shown to play a role in RNA processing, including splicing (such as HNRNPs F, H1, and H2), RNA trimming (POP1) and RNA decay (ZAP) [23][24][25] .…”
Section: Sars-cov-2 Prf Rna Capture Identifies Novel Host Interactorsmentioning
confidence: 99%
“…Proteomic studies further showed that SARS-CoV-2 reshapes cellular translation, splicing, carbon metabolism, protein homeostasis, and nucleic acid metabolism [143]. In addition to viral proteins, it was shown that SARS-CoV-2 RNA directly and specifically binds and/or modulates a broad network of human proteins in infected human cells [145], and host mitochondria serve as an organelle platform for anti-SARS-CoV-2 immunity [146].…”
Section: Virus-host Interaction and Exploitation Of The Cellular Machinerymentioning
confidence: 99%